Spanish seamen (circular) - Tewson, Vincent
025-0026-001 Telegraphic Address: TRADUNIC, SOWEST, LONDON. Telephone: Victoria 9020. Trades Union Congress GENERAL SECRETARY SIR WALTER CITRINE KBE To whom all communications should be addressed. Department International Our ref. HVT/AC/DT/720. Your ref. TRANSPORT HOUSE, SMITH SQUARE, LONDON, S.W.1. 14th March, 1940. SPANISH SEAMEN. We have received enquiries from one or two ports about emigration to Mexico and South America, and we have made certain tentative approaches at this end, which lead us to believe that certain limited facilities may be available for some of the men and their dependants in this country. Will it be possible, when you are making arrangements this week end to pay the men their grants, to interview them and to let me have the names of any men who wish to apply for inclusion in such a scheme of emigration? Please impress upon the men that they should not refuse any offers of employment which arise in the meantime as our efforts may prove unsuccessful. Please let me have particulars on the attached form of all applicants, if possible by MONDAY morning next, 18th instant. I am sorry that I am compelled by a combination of circumstances to ask you to deal with this matter in such a sunmary fashion, but the time is very short if we are to snatch a very thin chance of assisting some of the men in this way. Yours sincerely, H. V. TEWSON, Form. Assistant Secretary. 292/946/25b/22